Relasi Sosial NGO PERMAI Dalam Pemenuhan Pendidikan Terhadap Anak Migran Yang Tidak Berdokumen Di Pulau Pinang Malaysia - Sahureka, Danil (Universitas Maritim AMNI Semarang, 2024)
Undocumented migrant children lose access to formal education. Therefore, a learning forum is provided, namely the guidance studio (SB) or Learning Center. This research uses a qualitative method using a case study approach. The aim of this research is to determine the form of social relations of NGO PERMAI in building a guidance studio for undocumented migrant children, to find out the form of support/contribution from related parties in helping fulfill education for migrant children. The theory used is Michel Foucault's theory of power relations. The results of this research are: The PERMAI NGO guidance studio requires support and assistance from other parties, this form of relationship is a collaborative relationship from (KBRI, ​​KJRIl, PPI and students from universities in Indonesia). The forms of support provided vary, such as material support or learning needs (desks, chairs, notebooks, boards, etc.) or support in the form of personnel as provided by PPI.